The political theory of Aristophanes : explorations in poetic wisdom - Mhire, Jeremy J., 1977-; Frost, Bryan-Paul, 1961- (SUNY Press, 2014)
His original and wide-ranging collection of essays offers, for the first time, a comprehensive examination of the political dimensions of that madcap comic poet Aristophanes. Rejecting the claim that Aristophanes is little more than a mere comedian, the contributors to this fascinating volume demonstrate that Aristophanes deserves to be placed in the ranks of the greatest Greek political thinkers. As these essays reveal, all of Aristophanes' plays treat issues of fundamental political importance, from war and peace, poverty and wealth, the relation between the sexes, demagoguery and democracy to the role of philosophy and poetry in political society. Accessible to students as well as scholars, "The Political Theory of Aristophanes" can be utilized easily in the classroom, but at the same time serve as a valuable source for those conducting more advanced research. Whether the field is political philosophy, classical studies, history, or literary criticism, this work will make it necessary to reconceptualize how we understand this great Athenian poet and force us to recognize the political ramifications and underpinnings of his uproarious comedies